Components of Financial Stability of Credit Institutions: A New Perspective and New Horizons - Anatolievich, Davydov Vyacheslav; Ivanovich, Lavrushin Oleg; Evaldovna, Sokolinskaya Natalia; Khamitovna, Khalilova Milyausha (Journal of Reviews on Global Economics, 2018)
The article discloses a financial model characterizing the stability of credit institutions. In addition to the traditional quantitative indicators of the bank's activities, such as capital, assets, profit of the credit institution and others, relative indicators are of particular importance for assessing the effectiveness of banking activities. It is necessary to evaluate both quantitative and qualitative indicators of the activity of credit institutions, the synergy of which will enable them to identify the components of financial soundness and their assessment. An assessment of the financial stability of an individual credit institution is possible only based on the results of a comparison with the industry average components of financial stability. Particular attention is paid to such a component of assessing the financial stability of banks, as the effectiveness of the settlement of troubled debts. The authors of the article developed an alternative system for choosing a strategy for resolving the problem debt of credit institutions based on the qualimetric model. The idea and motivation (idea, purpose, motivation) The idea of the analysis is to study the validity and completeness of the hypotheses in accordance with which a study was made of financial stability of credit institutions and its impact on the willingness of customers and investors of banks to place their funds with them, as well as their possible outflow or counteraction to it depending on compliance their market discipline, the level and quality of risk management, as well as the availability of transparent and reliable information about the financial situation.